2017
DOI: 10.1159/000480516
|View full text |Cite
|
Sign up to set email alerts
|

pTis and pT1a Ipsilateral Breast Tumor Recurrence Is Associated with Good Prognosis after Salvage Surgery

Abstract: Objectives: Patients with ipsilateral breast tumor recurrence (IBTR) after breast-conserving surgery have a poor prognosis. There is little information regarding the prognostic impact of the tumor size in patients with IBTR. Methods: A total of 143 patients who had histologically confirmed IBTR without distant metastases and who underwent salvage surgery between 1989 and 2013 in our hospital were included. Distant disease-free survival (DDFS) was calculated according to the invasive tumor size of IBTR. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some risk factors for recurrence among women who underwent NSM, such as basal-like subtype or extended intraductal component, are recognized risk factors for an unfavorable prognosis independently by surgical strategy [40][41][42]. By sparing the skin and, in some selected cases, the NAC, the risk of leaving some occult residual neoplastic foci and the recurrence rate increases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some risk factors for recurrence among women who underwent NSM, such as basal-like subtype or extended intraductal component, are recognized risk factors for an unfavorable prognosis independently by surgical strategy [40][41][42]. By sparing the skin and, in some selected cases, the NAC, the risk of leaving some occult residual neoplastic foci and the recurrence rate increases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the axilla in cases of breast cancer recurrence ( 76 ): • If SLNB or limited axillary dissection (fewer than ten lymph nodes have been removed) was previously performed and the patient is currently cN0 staged, reSLNB (ALND for positive SLN) or ALND is recommended. In case of or cN+ ALND is the treatment of choice.…”
Section: Surgical Treatment Of Locoregional Recurrencesmentioning
confidence: 99%
“…It has been reported that the poor prognosis is principally due to local tissue invasions, early tumor metastasis to regional lymph nodes, and the differentiation types of tumor cells [10] . An important prognostic factor for pancreatic carcinoma is the presence or absence of lymphatic and venous invasion.…”
Section: Introductionmentioning
confidence: 99%